Analysis of Factors Affecting Mathematics Learning Outcomes With Internal Locus of Control As a Mediator - Taningrum, Novita Suci Yuen; Ahadiyah, Kurnia; Septianawati, Erni (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Mathematics learning outcomes are optimal when an individual reaches a level of achievement that aligns with their potential and abilities. The factors that influence student learning outcomes come from two main aspects: external factors and internal factors. External factors include the influence of family, school, and the community environment, while internal factors encompass psychological dimensions, physical conditions, and the student's level of fatigue. This research analyzes the factors influencing mathematics learning outcomes through the internal locus of control as a mediator. The type of research is a survey with a quantitative approach. The research location was carried out at SMAN 2 Kediri City. The population of this study were all class XI students of SMAN 2 Kediri City. The sampling technique is simple random sampling, with a sample size of 100 SMAN 2 Kediri City students. Data collection techniques use family socioeconomic status questionnaires, psychological distress questionnaires, internal locus of control questionnaires, and third-semester student report cards. Data analysis was carried out using descriptive statistical analysis and inferential statistics. The research results show that (1) family socioeconomic status influences mathematics learning outcomes, (2) psychological distress influences mathematics learning outcomes, (3) internal locus of control influences mathematics learning outcomes, (4) internal locus of control cannot mediate between family socioeconomic status and mathematics learning outcomes, (5) internal locus of control can mediate between psychological distress and mathematics learning outcomes, and (6) the model in the research is acceptable.